HLA antibody repertoire in infants suggests selectivity in transplacental crossing - Savulescu, Dana M.; Groome, Michelle; Malfeld, Susan C. K.; Madhi, Shabir; Koen, Anthonet; Jones, Stephanie; Duxbury, Vania; Scheuermaier, Karine; De Assis Rosa, Debbie; Suchard, Melinda (American journal of reproductive immunology (1989), 2020)
Problem Late in pregnancy, women produce and transfer high amounts of antibodies to the foetus. During gestation, women produce antibodies against human leukocyte antigens (HLA), including antibodies directed at foetal HLA. There is paucity of data on transplacental crossing, specificity and role of HLA antibodies in pregnancy and new‐borns. Method of study Using highly sensitive Luminex technology, we measured prevalence of IgG HLA antibodies in 30 mother‐infant pairs six weeks post‐partum. Additionally, in six pregnant women, we measured HLA antibodies longitudinally and HLA‐typed infant DNA to assess whether maternal HLA antibodies were directed at infant specificities. Results Overall, 68% of mothers and 44% of infants expressed HLA‐I antibodies and 56% of mothers and 52% of infants expressed HLA‐II antibodies. Infants shared up to 78% of antibodies with their mothers, suggesting that the remaining antibodies were self‐made. Less than 25% of maternal HLA antibodies were detected in infants, possibly due to selection in transplacental crossing. We detected complement‐fixing HLA antibodies in mothers and at low levels in infants. In a third of our pregnant subjects, we detected infant‐directed HLA antibodies. Conclusion Our findings raise the possibility of selection in transplacental crossing of HLA antibodies. As HLA antibodies may act as autoantibodies in the neonate, the mechanism of a selective transfer may give important insights into immune tolerance. Findings also suggest that infants start producing their own HLA antibodies in the first weeks of life, which, together with maternally derived antibodies may impact the infant's immune reaction to HLA proteins.